Extracellular sheath formation by Sphaeropsis hypodermia and association with its infection in elm trees - Ouellette, G.B.; Rioux, D.; Bussières, G.; Simard, M.; Bernier, L. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
Sphaeropsis hypodermia, isolated from a cankered American elm branch, was grown on agar medium (PDA), on autoclaved wiping paper (Kimwipes), and American elm (Ulmus americana) wood chips, or inoculated into greenhouse-grown American elm saplings. Samples from each treatment were double-fixed with glutaraldehyde and osmium tetroxide and examined with the light and the transmission electron microscopes. Ultrastructurally, the hyphae on PDA and inert substrates appeared surrounded by large extracellular sheaths which were delimited by rigid opaque bands of various thicknesses. The sheaths extended appreciable distances from the fungal cells, as evidenced by their adherence to rigid substrates. Individual or aggregated opaque bodies, even as large masses on elm wood chips, were the main components of the sheath. This opaque material was often associated with penetration and ruptures of the wood cells. Inoculated into elm trees, the fungus rapidly caused pronounced alterations of cambial tissues and colonized the adjoining bark and xylem cells. The prominent penetration and breakdown of the inner and outer bark cells by the fungus were associated with opaque material, particularly in cortical fibres. The material was structurally similar to the sheath formed on the rigid sterilized substrates. In the xylem, only the walls of the recently deposited cells were visibly altered, and although mature fibres were generally colonized, the passage of the fungus from one fibre to another was rarely observed, contrary to the passage from vessel and ray cells to adjoining cells. In that instance, only bands of opaque material present in the walls of fibres were connected with fungal cells in their lumen. In the inner bark and cambial regions, cell hypertrophy and hyperplasia occurred next to host walls that were altered and contained similar opaque material. The extracellular sheath of S. hypodermia under in vitro conditions and the opaque material associated with host wall alterations in vivo are considered to be analogous.